The Main Controlling Factors and Evaluation Method of the Reservoir Stimulation Potential: A Case Study of the Changning Shale Gas Field, Southern Sichuan Basin, SW China - Shen, Cheng; Zhao, Jinzhou; Xie, Jun; Fu, Yongqiang; Wu, Jianfa; Ren, Lan (Frontiers in Earth Science, 2021)
Based on logging, seismic, fracturing and production data from 301 productive wells in Longmaxi Formation in Changning shale gas field of southern Sichuan basin, the various influence factors of shale gas stimulated potential have been analyzed to carry out the correlation study with estimated ultimate recovery (EUR) of the same fracturing operation intensity to fully clarify the main controlling factors for shale gas stimulated potential. The results show that matrix brittleness, fracture propagation and reservoir properties are the 3 key secondary potentials that control shale gas stimulation potential. The matrix brittleness is controlled by elastic modulus, Poisson’s ratio, Type I and II fracture toughness, which reflects the uniformity of hydraulic fracture propagation. Fracture propagation is controlled by critical net pressure, which reflects the scale of hydraulic fracture propagation. Reservoir properties are controlled by porosity, total organic carbon content (TOC) and horizontal interval differences, which reflect the enrichment conditions and dynamic production capacity of reservoir resources. The matrix brittleness index, fracture propagation index, reservoir properties index and their combined stimulated potential index were formed by using the above 7 parameters to verify and apply the wells in Changning shale gas field. Results show that the matrix brittleness index and length-width ratio of hydraulic fracture was significantly negative correlation, the fracture propagation index and stimulated reservoir volume (SRV) were significantly positive correlation, stimulated potential index was developed taking into account enrichment & exploitation potential. In areas where the value is greater than 0.5, increasing the fracturing scale can effectively improve the well productivity; in areas less than 0.5, increasing the fracturing scale has an upper limit on the increase of productivity, so the physical properties of the reservoir itself play a significant role in controlling the production of shale gas wells.